Anxiety and depressive disorders in an emergency department ward of a general hospital: a control study. Issue 2 (26th February 2004) - Marchesi, C; Brusamonti, E; Borghi, C; Giannini, A; Di Ruvo, R; Minneo, F; Quarantelli, C; Maggini, C
Abstract : Objective: In this study anxiety and depressive disorders were evaluated in patients admitted to an emergency department (ED) or to a medical department (MD). Methods: The General Health Questionnaire-30 (GHQ-30) was administered to screen all patients (n = 719) consecutively admitted to an ED (n = 556) and to MD (n = 163) in a 120 day period. All GHQ-30 positive (score>4) underwent the Mini International Neuropsychiatric Interview, a structured interview to diagnose mental disorders according to DSM-IV criteria. Results: Subjects positive to GHQ-30 were 264 (47%) in ED and 88 (54%) in MD. A mental disorder was diagnosed in 233 ED patients (42%) and in 77 MD patients (47%) (p = 0.70). The most frequent disorders were anxiety disorders in ED patients (18.1%) and depressive disorders in MD patients (21%) (p = 0.04). Conclusions: Anxious patients more frequently seek attention at ED, whereas patients with depressive disorders are more often observed in medical units. The improvement of quality of care, the waste of healthcare resources through unnecessary medical care, and the well known efficacy of appropriate treatments in patients with anxiety and depressive disorders make the diagnosis of these patients particularly important.